Carbon Cycle in the Changing Arid Land of China Yanqi Basin and Bosten Lake (Springer Earth System Sciences,, 2018)
This book integrates the analyses of organic carbon and carbonate accumulation in soil and lake sediment in a typical arid region of China that has experienced significant climate and land-use changes. It demonstrates that carbonate accumulation greatly exceeds organic carbon in both soil and sediment. It also shows that intensive cropping with sound land management in the arid land not only increases soil organic carbon stock, but also enhances accumulation of soil carbonate, particularly in subsoils. Carbon accumulation in the lake sediment increased between 1950 and 2000, after which it declined, and the authors explore how human activity and climate change may have caused the changes in carbon burial in the lake sediment. This book is of interest to researchers in a number of fields such as soil science, limnology and global change, as well as to the policy-makers.